The efficacy of artemether and primaquin versus chloroquine-primaquine on uncomplicated malaria: A study on children in Kokap, Samigaluh area, and Oirimulyo Puskesmas, Kulon Progo - Margareta Yuliani Margareta Yuliani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Malaria is one of infectious diseases influencing mortality of newborns, infants, and delivering mothers, Chloroquine is a standard anti-malaria or fist-line antimalarial drug for treatment and chemoprophylaxis of susceptible uncomplicated malaria in Indonesia. Increased resistance toward standard medications turns out to be one of difficulties in malaria prevention, especially in endemic areas. To solve the problem, a new antimalaria drugs i.e. artemether is now under extensive studies. Objective: To know the efficacy of artemether-primaquine therapy compared to chloroquine-primaquine therapy in children with uncomplicated malaria.Methods: Sixty-three children were enrolled in this study through active case detection (ACD) and passive case detection (PCD) from April to July 2004 in Kokap, Samigaluh and Girimulyo Puskesmas, Kulon Progo; they fulfilled inclusion criteria of uncomplicated malaria, were willing to participate in 28-day study by signing informed consent form. Subjects were randomly divided into two groups of treatment. Clinical and parasitological observation were done on DO, D1, D2, D3, D7, D14, D21, D28. WHO (2003) therapeutic response criteria was used to evaluate the therapeutic efficacy. The result of academic clinical and parasitological response (ACPR) was compared to treatment failure (early treatment failure/ ETF and late treatment failure/LTF). Statistical analysis was done using Pearson X2.Results: Final results revealed that artemether-primaquine group showed ACPR and failed therapy of 30/ 32 (93.8%) and 2/32 (6.3%) respectively, while chloroquine-primaquine group 22/31 (71%) and 9/31 (92%) respectively. These results were statistically significant (p<0.05). The average rate of fever clearance time (FCT) and parasite clearance time (PCT) in artemether-primaquine group were 24.63 t 8.65 hours and 32.61 t 13.1 hours, respectively, while in chloroquine-primaquine group were 42 ± 8.65 hours and 32.61 t 18.9 hours, respectively. Nausea and abdominal pain as side effects of both therapy occurred in 18.8% and diarrhea in 6.3% of subjects, they recovered with no treatment. In chloroquine-primaquine group nausea or vomiting were found in 22.6% of subjects; in addition abdominal pain, headache, blurred vision and itching in 12.9%, 32.3%, 6.5%, and 3.2% respectively.Conclusion: Artemether-primaquine showed better therapeutic efficacy (92,8%) compared to chloro- quine-primaquine (71%) on children with uncomplicated malaria. Key words: artemether-primaquine - chloroquine-primaquine - uncomplicated malaria - therapeutic response side effects